Assessing the impacts of watershed interventions using ground data and remote sensing: a case study in Ethiopia - Gumma, Murali K.; Desta, G.; Amede, T.; Panjala, P.; Smith, A. P.; Kassawmar, T.; Tummala, K.; Zeleke, G.; Whitbread, Anthony M. (Springer, 2022)
Quantifying the temporal and spatial changes due to watershed interventions is important for assessing the effectiveness of natural resource management practices on vegetative cover and sediment management. This study assessed the performance of natural resource management in a target site (Aba Gerima) and compared the collateral impacts on neighbouring watersheds in Ethiopia in terms of land-use land-cover change. Changes in the extent of cropland, grassland and shrubland were assessed in the target watershed and the non-treated neighbouring watersheds using temporal satellite imagery. In addition, ground monitoring was applied to quantify the impacts on sediment accumulation, fodder biomass and vegetative cover intensity. The study findings showed substantial changes over the study period: mainly, a change from degraded and barren land to restored vegetation in the target watershed, but a continued trend of land-use change from perennial vegetation to cropland in the neighbouring untreated watersheds. There was a decrease in the rate of conversion of vegetative land cover to cropland in the target watershed, and significant on-site changes in sediment retention, fodder productivity and vegetation intensity. The study findings demonstrate a link between management interventions and improvement in soil and vegetation ecosystem functions. These results not only indicate that watershed-level interventions improve on-site soil and water environmental services but also underline the role of community managed land-use regulations in reducing pressure on natural land-use systems and thereby serve the major goal of up-scaling sustainable land management.